ANALISIS LAPORAN ARUS KAS UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAAN FOOD & BAVARAGE TAHUN 2017-2020 - Nurul Alfian; rohmaniyah rohmaniyah; Runik Puji Rahayu; Muslimatul Aina; Andriani Kusuma (Aktiva : Jurnal Akuntansi dan Investasi, 2022)
The statement of cash flows is a summary of cash inflows and cash outflows which in its financial format are divided into groups of operating activities, investing activities and financing activities. The cash flow statement provides information that enables users to evaluate changes in a bank's net assets, financial structure and ability to influence the amount and timing of cash flows in order to adapt to changing circumstances and opportunities.This type of research is descriptive qualitative, namely collecting data. The purpose of this study is to determine the financial performance of Food & Beverage Tbk companies during 2017-2020. The method used is ratio analysis, where the ratios used in this study are the ratio of operating cash flows, the ratio of operating cash flows to interest, the ratio of capital expenditures, the ratio of total debt, and the ratio of cash flows to net income. There are 5 companies that are used as a cash flow ratio analysis, namely PT. Tiga Pilar Sejahtera Food Tbk, PT. Delta Djakarta Tbk, PT. Mayora Indah Tbk, PT. Nippon Indosari Corpindo Tbk, and PT. Ultra Jaya Milk Industry & Trading Company Tbk.